Complexos mono, bi e trinucleares de metais de transição com bases de Schiff tridentadas tipo ONN e tetradentadas do tipo ONNO : síntese, caracterização e estudos como catalisadores na oxidação de catecois - Silva, Ricardo Soares Mota (2015)
Salen-type complexes are an important class of coordination compounds, which have been used to catalyze a wide variety of reactions in various homogeneous and heterogeneous systems. Complexes of transition metals are very versatile and participate in many chemical processes, which make the study of these very interesting. Research shows that the complexes of salen [salen = N, N'-ethylenebis (salicilidenoamina)] are efficient catalysts, and some compounds of this type have been investigated as catalysts in the oxidation of catechol. In this work were synthesized six types of compounds, ligands, symmetric mononuclear complexes, tridentate complexes, asymmetric mononuclear complexes, binuclear and trinuclear complexes. The series have satisfactory yields. The synthesized compounds in this work were characterized by melting point, elemental analysis, vibrational spectroscopy in the IR region, absorption spectra in the UV-vis, conductivity measurements and solubility. The ligands and three palladium(II) complexes were also characterized by nuclear magnetic resonance. From these characterizations, comparisons were made between ligands, mononuclear, tridentate, binuclear and trinuclear complexes, and also with respect to the effects of the substituents on the aromatic ring at positions 4 and 5. The kinetics was performed using a spectrophotometer, following the formation of the product derived from oxidation of 3,5-di-tert-butylcatechol at 400 nm. In kinetic study were tested the binuclear and the trinuclear complexes which showed catalytic activities compatible with those of similar complexes described in the literature, among them we can mention the binuclear complexes [Cu(Cu(t-4DEA-salcn))Cl2] e [Cu(Cu(t-5NO2- salcn))Cl2] , kcat = 0,132 s-1 e kcat = 0,108 s-1, respectively; and the palladium(II) copper(II) binuclear complexes [Cu(Pd(t-salcn))Cl2] e [Cu(Pd(t-4-DEA-salcn))Cl2], kcat = 0,113 s-1 e kcat = 0,240 s-1, respectively.